Konsep Kemiskinan Kultural - Palikhah, Nur (Alhadharah: Jurnal Ilmu Dakwah, 2016)
"Sufficient" worldview for the Javanese community, especially farmers as their values, that is to say they are satisfied, peaceful and calmly with what they get. Javanese peasants working in the fields not for profit, but merely to fulfill the purposes of simple everyday family life. When one shoulder (0.7 ha) of rice fields were planted with a single crop in a year is enough to meet the needs of a family life, then the farmer would not want more than that. What is the meaning and purpose of life if not to achieve peace and inner satisfaction. This view of life such as lack of work ethic is one of the few values or culture that is embraced by the poor due to the culture of poverty where poverty has emerged as a result of the values or culture embraced by the poor.Pandangan hidup âmencukupiâ bagi masyarakat Jawa terutama petani menjadi nilai yang mereka anut, artinya mereka sudah merasa puas, tenteram, dan ayem dengan apa yang mereka dapatkan. Petani Jawa bekerja di sawah bukan untuk mencari keuntungan, tapi sekedar untuk mencukupi keperluan hidup sehari-hari keluarganya yang sederhana. Bila dengan satu bahu (0.7 ha) sawah yang ditanami dengan sekali panen dalam setahun sudah cukup untuk memenuhi keperluan hidup sebuah keluarga, maka sang petani tidak akan menginginkan lebih daripada itu. Apalah arti dan tujuan hidup ini kalau bukan untuk mencapai ketenangan dan kepuasan batin. Pandangan hidup ini seperti kurang memiliki etos kerja merupakan salah satu dari beberapa nilai-nilai atau kebudayaan yang dianut oleh orang miskin yang disebabkan karena adanya kebudayaan kemiskinan dimana kemiskinan muncul sebagai akibat adanya nilai-nilai atau kebudayaan yang dianut oleh orang miskin.Â